2014
DOI: 10.3139/146.111018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between austenite stability and martensite formation in modified 9Cr-1Mo steel

Abstract: Aimed at investigating the relationship between austenite stability and martensite formation in modified 9Cr-1Mo steel, the fully austenitized steel was cooled to a temperature above or below the start temperature of martensite transformation (Mso, 406 °C), which occurs upon continuous cooling from the austenitizing temperature to room temperature, and held for different times (10 min, 25 min, and 45 min) followed by cooling to room temperature. The concept of primary and secondary martensite is introduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The M 23 C 6 carbide is rich in carbon and chromium [25]. The stability of meta-austenite will decrease after carbide precipitation due to the decrease of alloying elements [26]. But, matrix austenite can be retained at this temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The M 23 C 6 carbide is rich in carbon and chromium [25]. The stability of meta-austenite will decrease after carbide precipitation due to the decrease of alloying elements [26]. But, matrix austenite can be retained at this temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Tamura et al [49] suggested that the untransformed austenite would evolve into a new microstructure during subsequent tempering, which was related to the peaks in hardness and time to rupture of modified 9 wt% Cr steel. To obtain certain amount of retained austenite in 9 wt% Cr steels, after the austenization treatment, the steels can be cooled to a temperature between the martensite start temperature (M s ) and finish temperature (M f ) for different time [50] . At the interrupted cooling stage, the carbon partitions from the transformed martensite into the remaining austenite, increasing the stability of austenite and resulting in the film-like retained austenite between martensite laths.…”
Section: Retained Austenitementioning
confidence: 99%
“…Santella et al [16] report an incomplete austenite transformation in the weld metal of modified 9Cr-1Mo steel during initial cooling from an austenitizing treatment and the transformation of retained austenite to martensite during tempering, and attributed to the effects of microsegregation. The presence of retained austenite can be undesirable in the steel, if it is metastable, and can lead to the formation of untempered martensite or inhomogeneity after tempering [17]. Inhomogeneity in such steel components can have a significant negative impact on the mechanical properties, reducing the service life.…”
Section: Introductionmentioning
confidence: 99%